Brain functional connectivity dynamics at rest in the aftermath of affective and cognitive challenges. Issue 4 (24th November 2020) - Gaviria, Julian; Rey, Gwladys; Bolton, Thomas; Delgado, Jaime; Van De Ville, Dimitri; Vuilleumier, Patrik
Abstract: Carry‐over effects on brain states have been reported following emotional and cognitive events, persisting even during subsequent rest. Here, we investigated such effects by identifying recurring co‐activation patterns (CAPs) in neural networks at rest with functional magnetic resonance imaging (fMRI). We compared carry‐over effects on brain‐wide CAPs at rest and their modulation after both affective and cognitive challenges. Healthy participants underwent fMRI scanning during emotional induction with negative valence and performed cognitive control tasks, each followed by resting periods. Several CAPs, overlapping with the default‐mode (DMN), salience, dorsal attention, and social cognition networks were impacted by both the preceding events (movie or task) and the emotional valence of the experimental contexts (neutral or negative), with differential dynamic fluctuations over time. Temporal metrics of DMN‐related CAPs were altered after exposure to negative emotional content (compared to neutral) and predicted changes in subjective affect on self‐reported scores. In parallel, duration rates of another attention‐related CAP increased with greater task difficulty during the preceding cognitive control condition, specifically in the negative context. These findings provide new insights on the anatomical organization and temporal inertia of functional brain networks, whose expression is differentially shaped by emotional states, presumably mediating adaptive homeostatic processes subsequent to behaviorally challenging events. Abstract : Dynamic intrinsic functional connectivity brain networks were altered after exposure to negative emotional content and after emotionally influenced cognitive control. Both brain networks fluctuations were associated with changes in self‐reported affect state and cognitive control performance.